Preventing relapse in non-infectious uveitis affecting the posterior segment of the eye: evaluating the 0.2 μg/day fluocinolone acetonide intravitreal implant (ILUVIEN) - Bodaghi, Bahram; Nguyen, Quan Dong; Jaffe, Glenn; Khoramnia, Ramin; Pavesio, Carlos (Journal of ophthalmic inflammation and infection, 2020)
The current article is a short review of an Alimera Sciences-sponsored symposium held during The 15th International Ocular Inflammation Society Congress in Taiwan on the 14th November 2019 entitled, ‘Preventing relapse of non-infectious uveitis effecting the posterior segment of the eye - evaluating the 0.2 μg/day fluocinolone acetonide intravitreal implant.’
Gesehen am 06.11.2023